The 'fluid governance' of urban public spaces. Insights from informal planning practices in Rome. (April 2020) - Certomà, Chiara; Chelleri, Lorenzo; Notteboom, Bruno
This paper investigates the emergence of informal planning practices and their relationship with the new geometries of power and responsibility that characterise what is here defined and described as 'fluid governance'; and that leads to co-creative forms of public space governance. In particular, the research explores the key role played by some politically progressive forms of urban gardening in pivoting actions that transform green spaces through informal planning into areas for food production and collaborative management. This challenges traditional governance networks and re-defines the functioning of public spaces. The case of Parco delle Energie in Rome (Italy) serves as an example of a process of space re-appropriation, planning and finally co-management performed by a dense network of very diverse actors, who established a collaborative framework with the administration in order to re-shape decision-making dynamics. A comparative analysis of international cases confirms that urban gardening is challenging the dominance of a traditional planning perspective worldwide, both spatially as on the level of governance, and is turning citizens' dissensus into a productive force in the re-imagination and stewardship of public urban space. The conclusion suggests the self-design and co-managing capacities of urban gardeners and citizens could lead to adequate synergies between actors, enabling new urban governance models in line with the global ambition to build more sustainable and inclusive cities.